Strategi Pengembangan Karyawan Untuk Peningkatan Layanan Dalam Menyongsong Bank 4.0 Pada Bank Syariah Indonesia (Studi Kasus Area Jakarta Thamrin) - Khumaeroh, Siti; Raharja, Sapta; Zakaria, Fransiska R (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2024)
In readiness to implement banking strategies in the face of challenges and opportunities in the era of banking 4.0, infrastructure development is needed, one of which is the role of human resources, which is an asset in realizing the continuity of performance and improving the banking business that is expected to continue to progress and develop. This research is a case study conducted using a qualitative descriptive approach through in-depth interview methods to 7 experts who are experts in the field of banking experts and using questionnaires to 25 employees of Bank Syariah Indonesia in the Jakarta Thamrin Area in the DKI Jakarta Capital Region. The results of the IFE analysis obtained a total score of 2.78 with the strength factor is Bank Syariah Indonesia as a market leader in the Islamic banking industry and the weakness factor is that Islamic banking literacy for employees is still low and the results of the EFE analysis, a total score of 3.22 with the highest opportunity focus is the improvement of e-learning platforms that can improve employee training and the biggest threat is rapid technological changes that require new skills. The total score of internal and external strategic factors falls in the growth and development growth and build quadrant, quadrant I and the results of priority strategies are strategies for identifying employee needs and competencies, strategies for increasing literacy in Islamic banking and digital knowledge and strategies for using digital technology and innovation